1997
DOI: 10.1093/ajcp/108.1.13
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Specimen Adequacy in Fine-Needle Aspirates of Nonpalpable Breast Lesions

Abstract: Pathology-related medical malpractice claims frequently concern fine-needle aspirations (FNAs) of breast lesions, and diagnostic errors have been attributed in part to the inadequacy of the specimens. Cytologic criteria for adequate FNA specimens, specifically in cases without malignancy, have not been clearly defined.From January 1988, to August 1995, 669 ultrasonographicguided FNAs of nonpalpable, solid breast lesions with subsequent histologic examination were performed at our institution. From these, 54 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…17,21 By analysis of the surgical specimens, the latter appears to be the main factor in our study group. Sampling was relatively less of a problem because cytopathologists performed the majority of the breast FNAs in this study by, and immediate on site assessment for adequacy was routine.…”
Section: Cancer Cytopathologymentioning
confidence: 79%
See 1 more Smart Citation
“…17,21 By analysis of the surgical specimens, the latter appears to be the main factor in our study group. Sampling was relatively less of a problem because cytopathologists performed the majority of the breast FNAs in this study by, and immediate on site assessment for adequacy was routine.…”
Section: Cancer Cytopathologymentioning
confidence: 79%
“…Similar findings were reported in other studies. 21,30 It would not be practical, and usually would not be possible, to diagnose ADH on FNA considering the afore mentioned challenges in the histologic diagnosis of ADH.…”
Section: Cancer Cytopathologymentioning
confidence: 99%
“…5,11,14,16,17 Utilizing cell count as the criterion to define adequacy, our study included one case (1.6%) of a misinterpreted FNA with a subsequent, biopsyproven infiltrating ductal carcinoma. According to our definition of cellular adequacy, cellular material present on this smear was sufficient to make a suspicious diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This empirical observation has recently been substantiated by a study that showed that a significant proportion of breast aspirates may yield false negative results despite "adequate to high" cellularity. 5 Based upon the above rationale, we have specific recommendations for each cytologic diagnostic category. Although definitive treatment was recommended for our positive cases, a preceding confirmation of the malignant diagnosis by frozen section or gross examination is always prudent, especially for nonpalpable breast lesions detected on and sampled under the guidance of mammography, since a significant proportion of carcinomas in these specimens is in situ.…”
Section: Discussionmentioning
confidence: 99%